2013
DOI: 10.1103/physreva.88.042505
|View full text |Cite
|
Sign up to set email alerts
|

Shift and broadening of resonance lines of antiprotonic helium atoms in liquid4He

Abstract: The shift and broadening of the resonance lines in the spectrum of antiprotonic helium atoms pHe + located in fluid and superfluid 4 He have been estimated. The contributions to the shift and broadening from collective degrees of freedom in liquid 4 He have been evaluated using the phenomenological response function. The shift due to collisions ofpHe + with 4 He atoms has been calculated in the quasistatic limit using the experimental pair-correlation function. It has been shown that an implantedpHe + atom est… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…A similar study for liquid 4 He, presented in Ref. [1], showed that the shift is a linear function of density in normal-fluid 4 He and displays only small oscillations with temperature in superfluid 4 He. The pairdistribution function, which describes the atom distribution around a given particle, is very similar for both the normal-fluid and the superfluid helium at various temperatures and saturated-vapor pressure.…”
Section: Introductionsupporting
confidence: 55%
See 4 more Smart Citations
“…A similar study for liquid 4 He, presented in Ref. [1], showed that the shift is a linear function of density in normal-fluid 4 He and displays only small oscillations with temperature in superfluid 4 He. The pairdistribution function, which describes the atom distribution around a given particle, is very similar for both the normal-fluid and the superfluid helium at various temperatures and saturated-vapor pressure.…”
Section: Introductionsupporting
confidence: 55%
“…Thus, the knowledge of the pair-correlation function above this limit is not needed. The resonance-line shifts ∆E 0 which are presented in Table I display a clear nonlinear dependence on the target density, which is in contrast to the behavior of analogous line shifts in 4 He gas [5,6] and liquid 4 He above T = 2.17 K [1]. The absolute values of the reduced line shifts in solid helium are greater than the values of the corresponding line shifts in liquid 4 He (e.g., ∆E 0 /̺ = −0.427 GHz l/g for ̺ = 146 g/l at T = 2.27 K [1]).…”
Section: Collisional Shift Of Resonance Lines In Solid Heliummentioning
confidence: 78%
See 3 more Smart Citations